Relação parasito-hospedeiro na infecção de macrófagos por Clostridium chauvoei - Prhiscylla Sadanã Pires (2015)
Clostridium chauvoei is the etiologic agent of blackleg, a high mortality disease that affects calves. Despite the recognized importance of this disease, its pathogenesis and microorganism virulence factors have not been fully elucidated. Among the knowledge absences, there is the mechanism involved in C. chauvoei bowel traffic to the muscles. This step is essential for spore deposition in infection site, the agent would remain dormant until they find favorable conditions to germinate and multiply. In light of this, the aim of this study was to evaluate the survivability of C. chauvoei after internalization of murine macrophage RAW 264.7 lineage and bovine macrophage. It was evaluated the differences in survival rates of vegetative and spore C. chauvoei and the cytokine profile of transcripts induced by infection with one of these two bacterial form. The RAW 264.7 macrophages and bovine macrophages derived from peripheral monocytes were infected with C. chauvoei at multiplicity of infection (MOI) 1:50 with one of bacterial forms: vegetative or spore. The survival of C. chauvoei was assessed after 1 (T1), 24 (T24), 48 (T48) and 72 (T72) hours of infection. To assess the cytokine transcripts profile from bovine macrophages infected with C. chauvoei at MOI 1:50, it was evaluated the times T1, 6 (T6), 12 (T12) and T24 hours of infection. Cytokine transcripts that were measured: interleukin 10 (IL-10), IL-4, IL-12, IL-23 and growth factor beta (TGF-beta). C. chauvoei, both the spore and vegetative form, resist to microbicide macrophages process for 72 hours for infection. However, the lengthening of infection with vegetative form resulted in a decrease (p <0.01) in the number of viable internalized bacteria at T48. In contrast, the number of viable spores internalized was constant over the time of infection evaluated. There were any differences in survival between the infective forms (vegetative and spore) in infection with bovine macrophages throughout the study period (T72). Regarding the cytokine transcripts profile, it was observed that bovine macrophages infected with vegetative C. chauvoei owned a pro-inflammatory cytokines profile, such as IL-12 IL-23 (p <0.001). This profile could contribute to the microbicidal effects of these phagocytes. Contrariwise, when bovine macrophages were infected with spores of C. chauvoei, it was observed an anti-inflammatory cytokines profile, such as IL-10 and TGF-beta. This profile could cause the latency of this bacterial medium after macrophages internalization. The present results indicate that C. chauvoei the vegetative and sporulated form are able to resist to microbicidal macrophages effects. Nevertheless, spore form showed to be more resistant to death mediated by macrophages over a longer period infection. This is the first evidence that C. chauvoei is able of resisting the microbicidal effects of macrophages and the infectious forms (vegetative and spore) exhibit a diverging cytokine transcripts profile.